Fruit and cereal bioactives sources, chemistry, and applications - Tokusoglu, Ozlem; Hall, Clifford, III (CRC Press, 2011)
"Presenting up-to-date data in an easy-to-use format, this comprehensive overview of the chemistry of bioactive components of fruits and cereals addresses the role of these compounds in determining taste, flavor, and color, as well as recent claims of anticarginogenic, antimutagenic, and antioxidant capabilities. It provides detailed information on both beneficial bioactives such as phenolics, flavonoids, tocols, carotenoids, phytosterols, and avenanthramides and toxicant compounds including mycotoxins; aflatoxins, ocratoxin A, patulin, citrinin, cyclopiazonic acid, fumonisin, and zearalenon. A valuable resource for current knowledge and further research, it offers critical reviews, recent research, case studies, and references"--Provided by publisher.